The Fookien times Philippines yearbook, 1995-1996. (Fookien Times Yearbook Pub., 1995)
This yearbook is a comprehensive and valuable reference material covering all aspects of the past years' economy, politics and society in our country. It includes informative presentation of the highlights of significant events, both local like the "50th anniversary of the liberation of Manila" and international like the "Embassy Row" and "Our Diplomatic Abroad" articles.